1996
DOI: 10.1128/jcm.34.7.1765-1768.1996
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of teicoplanin-resistant coagulase-negative staphylococci

Abstract: Over a period of 5 years we have recovered 32 clinical isolates of coagulase-negative staphylococci (CoNS) exhibiting either decreased levels of susceptibility or true resistance to teicoplanin (MICs, 16 to 128 g/ml); these isolates make up 0.55% of the total CoNS isolated by us. Twenty-nine of the strains were also methicillin resistant, and all were susceptible to vancomycin. Fourteen of the strains were Staphylococcus epidermidis, fourteen were Staphylococcus haemolyticus, and four were Staphylococcus homin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…Even though development of vancomycin-resistant SCVs of Staphylococcus haemolyticus after exposure to vancomycin has been reported [13], resistance to teicoplanin might still be easier to obtain under selective pressure from vancomycin than resistance to vancomycin itself. Cercenado et al [14] found CoNS with reduced susceptibilities to teicoplanin but full susceptibility to vancomycin in 32 patients, eight of whom had been treated with vancomycin. Secondly, taking into account the tendency of SCVs to revert to the normal form, we cannot exclude the possibility that they developed spontaneously before vancomycin therapy but were missed in the corresponding blood cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Even though development of vancomycin-resistant SCVs of Staphylococcus haemolyticus after exposure to vancomycin has been reported [13], resistance to teicoplanin might still be easier to obtain under selective pressure from vancomycin than resistance to vancomycin itself. Cercenado et al [14] found CoNS with reduced susceptibilities to teicoplanin but full susceptibility to vancomycin in 32 patients, eight of whom had been treated with vancomycin. Secondly, taking into account the tendency of SCVs to revert to the normal form, we cannot exclude the possibility that they developed spontaneously before vancomycin therapy but were missed in the corresponding blood cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the emergence and spread of vancomycin resistance among Gram‐positive organisms have become matters of great concern [18–25]. Therefore, an important limitation for the prophylactic use of vancomycin is the possibility of selecting organisms resistant to this therapeutic agent [55].…”
Section: Approaches To Antibiotic Prophylaxis For the Prevention Of Imentioning
confidence: 99%
“…In one institution the rate of catheter‐related bacteremia increased from 20 episodes per 1000 admissions in 1986 to 50 episodes per 1000 admissions in 1993 [17]. In addition, the emergence of multiple‐resistant Gram‐positive organisms [18–25], which has made antibiotic therapy more difficult [26,27], is a matter of concern. Catheter‐related infections cause considerable morbidity, mortality rates of 10%–20%, as well as substantial medical costs, derived from diagnosis, treatment and prolongation of the patient’s in‐hospital stay [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Increased use of teicoplanin was correlated to an increase in MICs for teicoplanin in CNS [68]. In contrast, Cercenado et al [69] noticed that teicoplanin‐intermediate strains were exclusively isolated from a patient with no prior teicoplanin treatment. Recently, the emergence of glycopeptide resistance in CNS has been extensively reviewed by Biavasco et al [70].…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%